Layanan Kargo Udara Internasional di Bandar Udara Soekarno Hatta - Juanda Siahaan (Research and Development Agency of The Ministry of Transportation, 2011)
In the support of the international air cargo services as a safeguard against perpetrators of business rules required a government that can provide security and flight safety. Problems on the business of cargo service airports Indonesia prefers clear international rules such as place of transit cargo.For that Soekarno Hatta Airport as an international gateway facility serve as an example the development of the cargo terminal to be used as transit cargo. From the results of data acquisition is still felt less, both from the aspect of maintaining security and safety of the cargo until the cargo is received by the consignee. The solution to improving human resources in the handling of cargo and certainty in providing cargo services information